2022
DOI: 10.3390/plants11030292
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Canopy Traits Associated with Stay-Green Expression Are Closely Related to Yield Components of Wheat Genotypes with Contrasting Tolerance to Water Stress

Abstract: The onset and rate of senescence influence key agronomical traits, including grain yield (GY). Our objective was to assess the relationships between stay-green and GY in a set of fourteen spring bread wheat (Triticum aestivum L.) genotypes with contrasting tolerance to water stress. Based on leaf chlorophyll content index (Chl) and normalized vegetation index (NDVI) measurements, the senescence dynamics at leaf and canopy levels, respectively, were quantified. Parameters describing the dynamics of senescence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Canopy NDVI results indicated that senescence began prematurely due to water limitation (Moraga et al 2022). This shortening of the life cycle (shorter grain filling periods) and/or decreased ability of source organs to supply nutrients may have been associated with the lower yields under rainfed conditions (De Santis et al 2021).…”
Section: Water Stress Reduced Crop Yield and Biomass And Altered Grai...mentioning
confidence: 99%
“…Canopy NDVI results indicated that senescence began prematurely due to water limitation (Moraga et al 2022). This shortening of the life cycle (shorter grain filling periods) and/or decreased ability of source organs to supply nutrients may have been associated with the lower yields under rainfed conditions (De Santis et al 2021).…”
Section: Water Stress Reduced Crop Yield and Biomass And Altered Grai...mentioning
confidence: 99%
“…In order to achieve this goal, researchers used a combination of traditional phenotypic data and SSR markers to analyze the genetic diversity of candidate genotypes [7,[23][24][25]. Nevertheless, the use of high-throughput-origin indirect phenotypic data along with the SSR markers to explore wheat genetic diversity is scant [26,27]. Keeping this lacuna in mind, we used canopy-reflectance-based vegetation indices and yield parameters, as well as 30 SSR markers, to assess the genetic diversity of 56 bread-wheat genotypes under irrigated control and irrigation-simulated dry situations.…”
Section: Introductionmentioning
confidence: 99%
“…Maize is the largest grain crop planted in China and is an important source of food and industrial raw material. The essence of crop yield formation is the process of the sourcesink flow interaction, and the increase in the yield of stay-green crops is directly related to the maintenance of their photosynthetic capacity during the grain-filling period [25][26][27]. Determining the genetic basis of stay-green molecules is beneficial for cultivating new varieties of ideal plant types through molecular breeding methods, thereby comprehensively improving crop resistance to adverse conditions and improving their feeding value and yield potential.…”
Section: Excavation Of Key Genes In the Stay-green Mutant Contributes...mentioning
confidence: 99%